What are the Driving Forces Behind Spanish Publishers? - Magadán Díaz, Marta; Rivas García, Jesús Israel (Publishing research quarterly, 2022)
This research intends to perform a situation analysis of the Spanish publishing sector to see to what extent private publishing companies adequately interpret market signals and adapt to them. The study raises several questions for the Spanish publishing market: first, how is the price elasticity of the sale of copies?; second, what impact does the greater or lesser number of private publishers have on the sale of copies?; third, how does the sale of copies condition the evolution of the average print run?; and fourth, what impact does reading habit have on issue sales? The analysis carried out concludes: firstly, that the sale of copies is a price-elastic function to the price of books; second, that the greater the number of publishing agents, the higher the level of book sales; thirdly, those publishing companies adapt the average print runs per title in a period based on the copies sold on the market in the previous period and, finally, fourthly, the existence of a positive and direct relationship between the copy sales and the number of regular readers. Spanish publishers face digital transformation -and changes in their respective business models-, without losing sight of the variables studied that act as driving forces for their behavior and design their strategy in the market.
Keywords: publishing houses; book; situation analysis; print run; Spain; reading habits; Emerging; Scopus